The Influence of Organizational Culture and Work Involvement on Organizational Commitment in the Pamofit Korsabhara Baharkam Detacle, Republic of Indonesia Police Headquarters - M Rafli Yahya; Yuni Pratikno; Jamal Hanaffy (Dinasti International Journal of Digital Business Management, 2026)
Organizational commitment is a fundamental aspect in maintaining loyalty, engagement, and stability of personnel performance, especially in the Detachment of Pamofit Korsabhara Baharkam Headquarters of the Indonesian National Police which has high operational and discipline demands. Strong organizational commitment is influenced by various internal factors, including organizational culture and personnel work engagement. This study aims to analyze the influence of organizational culture and work engagement on organizational commitment, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 123 personnel of the Detachment of Pamofit Korsabhara Baharkam Headquarters of the Indonesian National Police as research respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPSS version 29 program. The results of the study indicate that partially organizational culture has a positive and significant effect on organizational commitment, with a t-value of 3.350 and a significance level of 0.001. In addition, work engagement also has a positive and significant effect on organizational commitment, with a t-value of 5.033 and a significance level <0.001. Simultaneously, organizational culture and work engagement have a significant effect on organizational commitment, as indicated by the F-count value of 22.380 with a significance of <0.001. The coefficient of determination (R Square) of 0.272 indicates that the two independent variables are able to explain 27.2% of the variation in organizational commitment, while the remaining 72.8% is influenced by other factors outside the research model. This finding confirms that strengthening a conducive organizational culture and increasing personnel work engagement on an ongoing basis are strategic factors in building and maintaining organizational commitment within the Detachment Pamofit Korsabhara Baharkam Mabes Polri environment